The Meaning of Toxic Relationship Communication for Teenagers - Zikri, Zikri Fachrul Nurhadi; Salamah, Ummu; Febrina, R. Ismira; Azni, Ensa Agnia (Jurnal Spektrum Komunikasi, 2024)
This research is motivated by the phenomenon of the rise of toxic relationships in romantic relationships among teenagers. This results in depression, suicide attempts due to excessive pressure from the perpetrator. Komnas Perempuan's annual records for 2022 contain 3,528 data on cases of violence in romantic relationships. The aim of this research is to explain the motives, experiences and meaning of toxic relationship communication in romantic relationships for teenagers in Garut Regency. The research method used is a descriptive method with a qualitative approach. Phenomenological theory becomes the scalpel in this research to obtain an explanation for the phenomenon of toxic relationships. Data collection techniques through participant observation, in-depth interviews, literature study and documentation. The data analysis techniques in this research are data reduction, data presentation and drawing conclusions. The research results show that the motives for toxic relationships in romantic relationships vary, starting from internal factors such as obsession, narcissistic personality disorder (NPD), excessive disclosure and external factors such as the surrounding environment and the presence of an ex-lover in a new relationship. The experiences of toxic relationships that many people experience are verbal and nonverbal violence, mild depression to severe depression, trauma, hampered personal development and loss of confidence in having new relationships with other people. The communication meaning of a toxic relationship is one-way communication, a relationship that hurts each other, does not have good expectations from the romantic relationship that is being carried out and the relationship is dominated by only one party.